Islamic Legal Thinking on the Fidyah Tradition of Death in the Barumun Community - Harahap, Abdul Aziz (International Tatho Academics, 2025)
The practice of fidyah is generally performed during the month of Ramadan according to the views of the scholars of the school of thought, but it can also be performed after the month of Ramadan. The criteria for those who fulfill fidyah also have stipulations, namely: the elderly, the severely ill, and pregnant and nursing mothers. The uniqueness that occurs in Barumun society is that fidyah is fulfilled by the heirs when the deceased passes away. This research discusses the practice of fidyah carried out by the Barumun community using the field research method and a descriptive-analytical approach. The results of this study indicate that the practice of fidyah among the Barumun community historically originates from Sheikh Ahmad Zein Hasibuan, who propagated this practice in his teachings. However, what Ahmad Zein explained was the practice of fidyah for fasting, not fidyah for prayer. Therefore, according to Islamic law, this practice is considered permissible by some muallim in Barumun sub-district. This research confirms that the practice of Islamic law can experience theoretical and practical developments along with the development of the literacy construction of Muslim religiosity.